A multicenter study of neurofibromatosis type 1 utilizing deep learning for whole body tumor identification - Cheng-Jiang Wei; Yan Tang; Yang-Bai Sun; Tie-Long Yang; Cheng Yan; Hui Liu; Jun Liu; Jing-Ning Huang; Ming-Han Wang; Zhen-Wei Yao; Ji-Long Yang; Zhi-Chao Wang; et al. (npj Digital Medicine)
Abstract Deep-learning models have shown promise in differentiating between benign and malignant lesions. Previous studies have primarily focused on specific anatomical regions, overlooking tumors occurring throughout the body with highly heterogeneous whole-body backgrounds. Using neurofibromatosis type 1 (NF1) as an example, this study developed highly accurate MRI-based deep-learning models for the early automated screening of malignant peripheral nerve sheath tumors (MPNSTs) against complex whole-body background. In a Chinese seven-center cohort, data from 347 subjects were analyzed. Our one-step model incorporated normal tissue/organ labels to provide contextual information, offering a solution for tumors with complex backgrounds. To address privacy concerns, we utilized a lightweight deep neural network suitable for hospital deployment. The final model achieved an accuracy of 85.71% for MPNST diagnosis in the validation cohort and 84.75% accuracy in the independent test set, outperforming another classic two-step model. This success suggests potential for AI models in screening other whole-body primary/metastatic tumors.